2017
DOI: 10.1002/lt.24778
|View full text |Cite
|
Sign up to set email alerts
|

Donor safety in living donor liver transplantation: The Korean organ transplantation registry study

Abstract: Major concerns about donor safety cause controversy and limit the use of living donor liver transplantation to overcome organ shortages. The Korean Organ Transplantation Registry established a nationwide organ transplantation registration system in 2014. We reviewed the prospectively collected data of all 832 living liver donors who underwent procedures between April 2014 and December 2015. We allocated the donors to a left lobe group (n = 59) and a right lobe group (n = 773) and analyzed the relations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
85
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 25 publications
5
85
2
Order By: Relevance
“…The outcomes of donors with an emergency evaluation were similar to those of donors for elective living liver donation. These results are similar to high‐volume LDLT centers throughout the world . These results show that emergency donor evaluation, if done in a protocolized manner, is safe with acceptable donor outcomes.…”
Section: Discussionsupporting
confidence: 76%
“…The outcomes of donors with an emergency evaluation were similar to those of donors for elective living liver donation. These results are similar to high‐volume LDLT centers throughout the world . These results show that emergency donor evaluation, if done in a protocolized manner, is safe with acceptable donor outcomes.…”
Section: Discussionsupporting
confidence: 76%
“…The authors reported that (i) they failed to reveal any relationship between transplant center experience and complication rate (especially bile tract complications and grade IIIb complications); (ii) the rate of complications could not be reduced, even toward figures lower than those of the former periods despite all kinds of training; (iii) they were disappointed by the absence of an expected drop in grade IIIa and grade IIIb complications; and (iv) biliary complications were more common among the younger patients. Lee et al observed serious complications in only 0.36% of 832 LDH cases and Kim et al in 4.5% of 288 LDH cases. However, Gruttadauria et al detected complications in 29% of 100 LDH cases, of which 21% were serious.…”
Section: Discussionmentioning
confidence: 97%
“…They reported that 12% of patients developed at least 1 complication: of these, 3.8% were major events (grade III, including 1 death), mostly related to biliary/bleeding events, and were twice higher after right hepatectomy. Lee et al [28] recently reviewed prospectively collected data from the Korean Organ Transplantation Registry of all 832 live liver donors who underwent procedures between April 2014 and December 2015. They reported no deaths after living liver donation and overall, biliary and major complication (grade ≥ III) rates were 9.3%, 1.7% and 1.9%, respectively.…”
Section: Morbiditymentioning
confidence: 99%
“…They reported no deaths after living liver donation and overall, biliary and major complication (grade ≥ III) rates were 9.3%, 1.7% and 1.9%, respectively. Based on this literature review, the right liver removal in the living donor was burdened with significant morbidity even in experienced surgical teams [28]. The mortality of this procedure (which remains a major hepatic resection) cannot be reduced below 0.3% [2].…”
Section: Morbiditymentioning
confidence: 99%